Role of Oxygen Vacancies in the Electrical Properties of WO3−x Nano/Microrods with Identical Morphology. (13th May 2018) - Shen, Zhenguang; Zhao, Zengying; Wen, Jian; Qian, Jingwen; Peng, Zhijian; Fu, Xiuli
Abstract : Tungsten oxide (WO3− x ) crystalline nano/microrods with identical morphology but different contents of oxygen vacancies were prepared by thermally evaporating fixed amount of WO3 powder in reductive atmosphere from different amounts of S power at 1150°C in a vacuum tube furnace, in which both sources were loaded in separate ceramic boat. With increasing amount of S powder, a series of tungsten oxides, WO3, WO2.90, W19 O55 (WO2.89 ), and W18 O49 (WO2.72 ), could be obtained. And devices were fabricated by screen-printing the obtained WO3− x crystals on ceramic substrates with Ag-Pd interdigital electrodes. With increasing content of oxygen vacancies, the devices fabricated with WO3− x crystals present a negative to positive resistance response to relative humidity. Under dry atmosphere, for the devices with increasingx, the strong response to light changed from short to long wavelength; under light irradiation, the conducting ability of the devices was enhanced, due to the more efficient separation and transportation of the photogenerated carriers; and under simulated solar irradiation, the photocurrent intensity of the W18 O49 device was roughly 8 times, about 500 times, and even 1000 times larger than that of the W19 O55, WO2.90, and WO3 one, respectively. With the versatile optoelectrochemical properties, the obtained WO3− x crystals have the great potential to prepare various humidity sensors and optoelectrical devices.